Exclusive Distribution and Non-Compete Clause in Trade: Transnational Agreements in European Union and United States - Hanni, Noona (Udayana Journal of Law and Culture; Vol 3 No 2 (2019): The Dynamics of Global Society, 2019)
Exclusive distribution agreements are commonly used in both European Union (EU) and United States (US) markets to ensure the efficient distribution of products and services. This article compares the competition legislation in the EU and US and focuses on the differences in the treatment of vertical agreements. This topic is addressed also from an economic perspective and focuses on the possible abuse of dominant market position by international multisectoral companies. This article focuses on the following legal and economic questions: how do competition legislations regulating vertical agreements differ in EU and US and, what kind of possible effects do transnational exclusive distribution agreements have on international trade and competition. In EU law exclusive distribution agreements, even those which include a non-compete obligation limited to five years, are considered as lawful restrictions on competition as long as they fulfil certain criteria listed in the Block Exemption Regulation. EU competition law recognizes the terms of block exemption and ‘safe haven’, whereas the US antitrust law does not regulate any exemptions to vertical restraints. Vertical restraints are interpreted in the US common law of antitrust in the light of the principle of Rule of Reason. An important difference in these jurisdictions is the definition of relevant markets, which is taken into consideration when evaluating the legality of a vertical agreement under competition law. Both jurisdictions emphasize the market power of the producer, but the allowed percentage of market share varies between EU and US and only EU legislation gives emphasis to the market power of the distributor. These differences in competition legislations regulating vertical agreements can lead to conflicts when interpreting the legality of a distribution agreement. The definition of relevant product markets might lead to big international multisectoral companies abusing their dominant position by entering into exclusive arrangements.